2019
DOI: 10.1111/jrh.12372
|View full text |Cite
|
Sign up to set email alerts
|

A Comparison of Pediatric Traumatic Injuries on Farms and Residences from 2009 to 2014

Abstract: Purpose Children injured on farms in the United States are hospitalized at 14 times the rate of children with injuries unrelated to farming. This study characterizes pediatric injuries occurring on farms compared to injuries in homes. Methods We examined the National Trauma Data Bank from 2009 to 2014 to identify children ages 0‐17 with ICD‐9 E‐codes reflecting a farm or residential place of injury occurrence. Appropriate nonparametric tests were used to compare patient, injury, and hospitalization characteris… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(17 citation statements)
references
References 24 publications
2
15
0
Order By: Relevance
“…For instance, prior literature of accident-related disparities has posited that environmental characteristics, specifically agricultural sources of employment among rural adolescents, may disproportionately expose rural children to trauma from excessive heat, dust, noise, pesticides and other chemicals, as well as exposure to machines that perform agricultural work. 5,26 Protocols and guidelines to lessen environmental exposures (eg, pesticides, chemicals, industrial waste) have the potential to lessen rural disparities in pediatric injuries. Other studies examining the disparity in childhood obesity have found that the rural built environment is less conducive to physical activity and healthy eating.…”
Section: T a G G E D H 2 Geography Distance And The Rural Environmenttmentioning
confidence: 99%
“…For instance, prior literature of accident-related disparities has posited that environmental characteristics, specifically agricultural sources of employment among rural adolescents, may disproportionately expose rural children to trauma from excessive heat, dust, noise, pesticides and other chemicals, as well as exposure to machines that perform agricultural work. 5,26 Protocols and guidelines to lessen environmental exposures (eg, pesticides, chemicals, industrial waste) have the potential to lessen rural disparities in pediatric injuries. Other studies examining the disparity in childhood obesity have found that the rural built environment is less conducive to physical activity and healthy eating.…”
Section: T a G G E D H 2 Geography Distance And The Rural Environmenttmentioning
confidence: 99%
“…Our observations are consistent with the observations of other authors. The structure of the trauma, the mechanisms of trauma, types of the injuries and the treatment methods are comparable to those of other centers treating children [11,12,13]. In publications from the USA, accidents related to moving agricultural machines, especially tractors, occur as often as in our material [4].…”
Section: The Situation In the Region And In The Worldmentioning
confidence: 61%
“…The analyzed material was consisted with other reports, and shown that the reasons for many accidents were also: the inappropriate pace of work, haste, insufficient concentration on the work performed, excessive physical effort, and severe weather conditions [11,12,13].…”
Section: Causes and Circumstances Of Accidentsmentioning
confidence: 99%
“…Children growing up on farms are exposed to higher levels of risk compared to children from the general population [ 1 , 2 , 3 , 4 ]. In our study, about a third of farm parents reported that a child had suffered an injury at some point that required medical attention.…”
Section: Discussionmentioning
confidence: 99%
“…In the United States of America (USA), farm children are exposed to significantly more risks of injury and fatality than the general population [ 1 , 2 , 3 , 4 ]. Every day, about 33 children are seriously injured in agricultural-related incidents, and about every three days, a child dies [ 1 , 5 ].…”
Section: Introductionmentioning
confidence: 99%